Analisis Peran Media Sosial (TikTok) dalam Dinamika Partisipasi Politik pada Pemilu Presiden 2024 - Rizanul, Reivania Calista; Egistin, Devira; Jasmine, Ahren; Juniarto, Damar (Journal of Social Contemplativa, 2025)
This article examines the role of the social media platform TikTok in shaping the dynamics of political participation during Indonesia’s 2024 Presidential Election. Using a qualitative approach, the study explores how TikTok facilitates political interaction, information dissemination, and public opinion formation. The focus is on the engagement of young voters, who dominate TikTok’s user base, and the digital campaign strategies employed by candidates and political parties. Findings reveal that TikTok serves as an inclusive space for political discussions, yet faces challenges such as misinformation and opinion polarization. This article offers insights into how social media not only broadens access to political participation but also shapes patterns of civic engagement in the era of digital democracy